Physical activity and health-related quality of life in chronic non-bacterial osteomyelitis - Nentwich Julia; Ruf Katharina; Girschick Hermann; Holl-Wieden Annette; Morbach Henner; Hebestreit Helge; Hofmann Christine (BMC, 2019)
Abstract Background Chronic non-bacterial osteomyelitis (CNO) is an autoinflammatory disorder of the skeletal system of yet unknown etiology. Patients present with local bone pain and inflammation and - to our experience - often suffer from functional impairment with significant disabilities of daily life. The objective of this study was to assess physical activity, fitness and health-related quality of life (HRQOL) in adolescents with established diagnosis of CNO versus healthy controls (HC). Methods 15 patients with CNO and 15 age and gender matched HC aged 13-18 years, completed questionnaires, performed an incremental exercise test with gas exchange measures up to voluntary fatigue and wore an accelerometer over 7 days at home to assess physical activity behavior. Results At the time of assessment, 5 CNO patients were in clinical, one in radiological and 5 in clinical and radiological remission. 7 did not receive any therapy at the time of assessment. The results of the exercise test and of the accelerometry did not show any significant difference between CNO and HC. However, reported sports participation was lower in patients with CNO and PedsQL3.0 and 4.0 showed significant lower values in most of the scores indicating reduced HRQOL. Conclusion Although most CNO patients showed a favorable course of disease without any relevant differences in objective measurements of physical activity and fitness versus HC at the time of assessment, questionnaires revealed perceived limitations. Further studies are needed to measure HRQOL and to validate questionnaires in patients with CNO against objective measures including more participants with a higher level of disease activity.